1999
DOI: 10.1165/ajrcmb.20.5.3458
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Regulation of Interleukin (IL)-1 β through Lung Epithelial Cells and Defective IL-1 Type II Receptor Expression

Abstract: Interleukin (IL)-1beta is produced primarily by activated mononuclear phagocytic cells in the lung airway and functions as a potent proinflammatory cytokine. Release of IL-1beta in the airway microenvironment induces the production of proinflammatory factors from parenchymal airway cells, including IL-8. To study the regulation of lung epithelial cell responsiveness to IL-1beta, the human type II-like airway epithelial cell line A549 and primary normal human bronchial epithelial (NHBE) cells were assayed for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 43 publications
4
32
2
2
Order By: Relevance
“…In vitro studies have suggested that blockade of both IL-1RII and IL-1ra activity enhances cellular responses to IL-1 (40). Our hypothesis is further strengthened by the recent report, which suggests that lung epithelial cells that lack IL-1RII are more susceptible to IL-1 and inflammatory mediators released by them (41).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In vitro studies have suggested that blockade of both IL-1RII and IL-1ra activity enhances cellular responses to IL-1 (40). Our hypothesis is further strengthened by the recent report, which suggests that lung epithelial cells that lack IL-1RII are more susceptible to IL-1 and inflammatory mediators released by them (41).…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, epithelial cells have been known to lack IL-1RII expression (41). Our experiments show that IL-1RII attenuates the effects of IL-1 in various cell types including rabbit and mouse synovial cells and human epithelial cells.…”
Section: Discussionmentioning
confidence: 53%
“…3C). This modest increase of NGAL is probably due to a higher basal activity of NGAL and/or a weaker response to IL-1␤ by NHBE cells (15). A slightly larger effect of IL-1␤ stimulation was observed in NHEK cells in which a 5-to 6-fold increase in NGAL was measured in the medium of cells induced for 48 h with IL-1␤ (20 ng/ml) relative to that from unstimulated cells and cells induced by TNF-␣ (20 ng/ml) at the same time points (Fig.…”
Section: Ngal Synthesis Is Up-regulated By Il-1␤mentioning
confidence: 99%
“…Previous studies have shown that IL-1␤ induces the production of IL-6 and IL-8 in A549 cells (14). We also compared the sensitivity of IL-1RII ϩ A549 epithelial cells to that of nontransduced cells with respect to the production of IL-6 and IL-8.…”
Section: Regulation Of Il-6 and Il-8 Production By Human Il-1rii ϩ Humentioning
confidence: 98%
“…We have recently shown, using gene expression arrays, that human cartilage and epithelial cells lack the expression of endogenous IL-1␤-antagonizing molecules such as IL-1RII and IL-1Ra (6,14). Both cell types play a profound role in the inflammation and pathophysiology of arthritis, thus making the cartilage and joints susceptible to low concentrations of endogenous IL-1␤.…”
Section: Lack Of Expression Of Il-1rii In Human Chondrocytes and Epitmentioning
confidence: 99%